Two pioneering studies on disability in popular culture and children’s literature - Schianchi, Matteo (Rivista di Storia dell’Educazione, 2020)
One of the first authors to have dealt with disability issues in the Italian context, from a perspective centred on the imaginary, popular culture and literature was the French René-Claude Lachal (1938-2003). Some of his texts are still unknown and still represent significant analysis on this subject.